A study of integration of risk management and value management in construction project - Lee, Swet Jean (2015)
Construction industry is one the main contributors for the growth of economic in Malaysia. Meanwhile, the process of construction project involves high risk and full of uncertainties. The issues that always happen are delay, over budget, out of scope and fail to achieve the objective. Risk management and value management are the best practice management tools to reduce the probability of risk and balance the cost and value of the construction project respectively. However, applying both of the management practices separately is waste of time and resources. Therefore, this research was conducted to identify the potentiality of the integration between risk management and value management and determine the benefits of the integration to the construction projects. The data was collected from targeted respondents who working at G7 construction company at Selangor. The data was analyzed by using SPSS 2.0 software. Pearson Correlation Test was used to analyze the relationship between the similarity factors and the potentiality of the risk management and value management to be integrated. Descriptive analysis used to identify the most significant benefits to the construction project. The results and findings provide the idea of the integration of both processes to project managers.